Legal Certainty and Justice Principles in Minimum Wage Determination under Government Regulation No. 51/2023 - Adhi Vieri Nico (Actual Insight, 2025)
This study examines the implementation of legal certainty in worker wage determination under Government Regulation No. 51 of 2023 on Wages by applying the principles of distributive, legal, and commutative justice. Using a normative juridical method with statute, case, and conceptual approaches, the research relies on primary legal sources, scholarly literature, and statistical data from the Central Statistics Agency. The analysis integrates doctrinal interpretation with a radar evaluation model covering ten dimensions, including legal certainty, accountability, justice, transparency, and sustainability. The findings reveal that the new formula, based on inflation, regional economic growth, and a region-specific index, supported by employment absorption and median wage, creates greater predictability and fairness in wage determination. Strengthening the role of Regional Wage Councils through a tripartite-plus mechanism enhances legitimacy and accountability. The study concludes that the regulation represents a significant innovation in Indonesia’s labor law, balancing business sustainability with worker welfare while advancing the realization of social justice mandated by Pancasila.